대학생의 건강증진 생활양식이 학업지연행동에 미치는 영향: 성별에 의해 조절된 투지의 매개효과 - 정구철(Goo-Churl Jeong) (한국콘텐츠학회 논문지, 20(12), 2020)
This study aimed to analyze the mediating effect of grit moderated by gender in the relationship between health promoting lifestyle and academic procrastination among 250 college students in the metropolitan area. As a result of the study, first, there was a significant positive correlation with grit for health promoting lifestyle, and significant negative correlation with academic procrastination. Grit had a significant negative correlation with academic procrastination. Second, grit had a significant mediating effect in the relationship between health promoting lifestyle and academic procrastination. Third, the mediating effect of grit in the relationship between health promoting lifestyle and academic procrastination was moderated by gender. In other words, it was found that men had a stronger mediating effect of grit than women. Based on these results, the role and importance of grit in the practice and maintenance of a health promoting lifestyle were discussed, and a way to practice health promoting behavior and coping with academic procrastination according to gender were suggested. 본 연구에서는 수도권에 거주하는 대학생 250명을 대상으로 건강증진 생활양식과 학업지연행동 간의 관계에서 성별에 의해 조절된 투지의 매개효과를 분석하였다. 연구 결과, 첫째, 건강증진 생활양식은 투지와 유의한 정적 상관관계가 있었고, 학업지연행동과는 유의한 부적 상관관계가 있었다. 투지는 학업지연행동과 유의한 부적 상관관계가 있었다. 둘째, 건강증진 생활양식과 학업지연행동 간의 관계에서 투지는 유의한 매개효과가 있었다. 셋째, 건강증진 생활양식과 학업지연행동 간의 관계에서 투지의 매개효과는 성별에 의해 조절되었다. 즉, 남성이 여성보다 투지의 매개효과가 더 강한 것으로 나타났다. 이러한 결과를 바탕으로 건강증진 생활양식의 실천과 유지에 있어 투지의 역할과 중요성을 논의하였고, 성별에 따른 건강증진 행위의 실천 방안과 학업지연행동의 대처 방안에 대해 제언하였다.